Cohesive zone parameters selection for mode-I prediction of interfacial delamination - Moslemi, Mohsen (Strojniški vestnik, 2015)
In order to determine the normal cohesive strength of composite laminates, a new test methodology was proposed. The values of cohesive zone parameters (the cohesive strength and the separation energy) for mode I interlamiar fracture of E-glass/epoxy woven fabrication were computed from a series of experimental tests. Cohesive zone model simulation based on interface finite elements was conducted. A modified form of the Park-Paulino-Roesler (PPR) traction-separation law together with a bilinear mixed-mode damage model was used to simulate the damage processes, using Abaqus cohesive elements. The numerical results were compared with experimental tests and confirmed the adequacy of normal cohesive strength. To ensure the sufficient dissipation of energy that successfully predicts delamination onset and propagation, cohesive zone length and minimum number of cohesive elements at cohesive zone length were determined. Interfacial penalty stiffness and the resistance curve of the composite specimen were also computed. The results show that the modified PPR model accurately simulates the fracture process zone ahead of the crack tip as compared to the bilinear model.
Keywords: delaminacija; model kohezivne cone; napovedovanje s končnimi elementi; normalna kohezijska trdnost